Ilha do Combú: um olhar sob as perspectivas conceituais do lazer e seus equipamentos - Maia, Arcanjo Miguel Garcia; Nunes, Jonathan Rodrigues; Cruz, Silvia Helena Ribeiro (Revista Brasileira de Ecoturismo (RBEcotur), 2017)
Este trabalho tem como objetivo apresentar à sociedade a Ilha do Combú, área que pertence a Belém do Pará e suas diversas formas de ser trabalhado. A partir da questão conceitual do lazer, procurar-se-á, a partir do empreendimento particular de Dona Nena (Filha do Combú), e da festividade de Santo Antônio, fazer uma análise da diversidade que compõe as comunidades que residem na ilha, porém que não são trabalhadas da melhor forma possível, tomando como ponto de partida as teorias de diferentes autores referidos à lazer, tentando ressaltar a potencialidade que a ilha abrange sob a ampla perspectiva do aproveitamento de horas livres, tantos de turistas quanto de residentes do munícipio de Belém, sabido que ambos são relevantes para a perspectiva do estudo sobre lazer. O trabalho finalizará, portanto, tentando fazer um consenso entre as diferentes teóricas dos autores para com a classificação da Ilha em sua totalidade, sob a ótica destes estudos sobre o tema do lazer, suas motivações, e seus referidos equipamentos e suas classificações.Island of Combú: the local community according to the conceptual perspectives of leisureABSTRACTThis paper has as objective approach the experience of Combú of the island community, place that belongs to Belém of the state of Pará, and due to the closeness to the capital while urban city has stronger relation with the visitation of eventual tourists whom haz the intection of approaching of green areas. Seeing that this flow produces na urbanizing impact in the area, the search proposed to approach the relation of the community with this new utility found in their place of everyday. Starting of the conceptual issue of leisure, it was made na analysis of yhe cultural and anthropological diversity that composes the families that reside in the island. And their relation with tourism. For such, it was made field visitis and open interview on the particular enterprise of Ms. Nena (Filha do Combú), and participant observation at the Santo Antônio de Piriquitatara festivity, one of the festivities that were occurring at the moment, seeking to pay attention to the frequencie and charactheristics on the recurrents tourists on site, as far as the perception of the local communnity to this touristic flow. The work endend trying to make na overview between the diferente theories of the authors to the island rating, both in relation to the use, as approaching the island as an equipment, and also in relation to the ends and motivations of tourists, always taking into account the percpetion of the local communnity.KEYWORDS: Local Culture; Leisure; Riveirine Communities; Tourist Development.